The burrow structure, colony composition and reproductive biology of the giant mole-rat (Fukomys mechowii) Peters 1881 from the Copperbelt of Zambia - Bennett, Nigel Charles (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2011.